On femininities in the Song of songs and beyond the most beautiful woman - Arbel, Daphna (London Bloomsbury Publishing Plc, 2022)
Cover -- Series -- Title -- Copyright -- Dedication -- Contents -- Plates -- Acknowledgments -- Introduction -- 1 On Ideal Femininity, Patriarchy, and Female Eroticism -- 2 On Many Shades of Femininity -- 3 On Conformity and Resistance through Dressing and Undressing -- Conclusion: The Most Beautiful Woman in the Song and Later Generations -- Bibliography -- Index of Biblical and Other Ancient Sources -- Index of Authors -- Index of Subjects.
Description based on publisher supplied metadata and other sources
Keywords: Bible.-Song of Solomon; Electronic books